Selection and results of the aberration computation and peculiarities of polarizing effect compensation in double UV monochromators for satellite-borne UV ozonometers - Vashchenko, V.; Loza, A.; Patlashenko, Zh. (Functional Materials, 2004)
Results of calculations are presented for optical-mechanical peculiarities of the doub le diffraction monochromator arrangement with dispersion subtraction based on spherical diffraction gratings for remote probing of the Earth’s ozonosphere from space platforms within the 255.5-339.8 nm spectrum range with the aim to obtain global mapping for vertical concentration profiles and total ozone content. Special requirements to the equip -ment installed at space platforms were also taken into account. The double diffraction monochromator, as well as a prismatic one, has its own polarizing impact on the measured radiation. Negligence or non-consideration of monochromator polarizing influence on spec-trometric measurements could cause an error up to 70 %. Experimental results show that the spectral sensitivity dependence on the measured radiation polarization is defined b y the system of dispersion elements and the input aperture value. A source of completely depolarized radiation was used for the measurements. To decrease the polarization effect of UV spectrometer, special depolarizers and polarizing effect compensators had been developed. Measurement results obtained with and without such devices have been com -pared to determine their work efficiency. Measurements were performed for all wavelengths of the spectrometer operating spectral range. Представлены результаты вычислений оптико-механических характеристик схемы двойного дифракционного монохроматора с вычитанием дисперсии на базе сферических дифракционных решеток для дистанционного зондирования озоносферы Земли с космических платформ в спектральном диапазоне 255.5-339.8 nm для глобального картографирования вертикальных профилей концентрации и общего содержания озона. При этом учитывались специальные требования для оборудования, устанавливаемого на космических платформах. Двойной дифракционный монохроматор, как и призменный монохроматор, имеет собственное поляризующее воздействие на измеряемое излучение. Пренебрежение поляризационным влиянием монохроматора на спектрометрические измерения может привести к ошибке до 70 %. Экспериментальные результаты показывают, что зависимость спектральной чувствительности на поляризацию измеряемого излучения определяется системой дисперсионных элементов и значением входной апертуры. Для измерения был использован источник полностью деполяризованного излучения. Для уменьшения эффекта поляризации УФ-спектрометра разработаны специальные деполяризаторы и компенсаторы эффекта поляризации. Проведено сравнение результатов измерения с использованием и без использования таких приборов для определения их рабочей эффективности. Измерение было выполнено для всех длин волн рабочего спектрального диапазона спектрометра. Наведеш результати обчислення оптико-механічних характеристик схеми подвійного дифракційного монохроматора з відніманням дисперсії, на базі сферичних дифракційних граток для дистанційного зондування озоносфери Землі з космічних платформ в спектральному діапазоні 255.5-339.8 nm з метою глобального картографування вертикальних профілів концентрації та загального вмісту озону. При цьому були враховані спеціальні вимоги до обладнання, що встановлюється на космічних орбітальних платформах. Подвійний дифракційний монохроматор, як і призмовий монохроматор, має власний поляризаційний вплив на випромінювання, що вимірюється. Нехтування монохроматора на спектрометричні вимірювання може привести до того, що помилка може досягнути 70 %. Експериментальні результати вказують, що залежність спектральної чутливості на поляризацію випромінювання, що вимірюється, визначається системою дисперсійних елементів і значенням вхідної апертури. Для вимірювання використовувалось джерело повністю деполяризованного випромінювання. Для зменшення ефекту поляризації УФ-спектрометра розроблені спеціальні деполяризатори та компенсатори ефекту поляризації. Проведено порівняння результатів вимірювання з використанням і без використання таких приладів для визначення їх робочої ефективності. Вимірювання було виконане для всіх довжин хвиль робочого спектрального діапазону спектрометра.